2019
DOI: 10.1101/543496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Networked information interactions of epileptic EEG based on symbolic transfer entropy

Abstract: Identifying networked information exchanges among brain regions is important for understanding the brain structure. We employ symbolic transfer entropy to facilitate the construction of networked information interactions for EEGs of 22 epileptics and 22 healthy subjects. The epileptic patients during seizure-free interval have lower information transfer in each individual and whole brain regions than the healthy subjects.Among all of the brain regions, the information flows out of and into the brain area of O1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…TE is an analytical method based on information theory that uses conditional probability to detect causal interaction or information flow between two signals. In contrast, several studies have shown that TE analysis can be applied to reveal disease-specific changes in functional connectivity in patients with Lewy body dementia or epilepsy [27], [28]. Both PLI and TE have revealed different aspects of functional connectivity concerning cognitive function in healthy as well as pathologically altered brain networks [26]- [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TE is an analytical method based on information theory that uses conditional probability to detect causal interaction or information flow between two signals. In contrast, several studies have shown that TE analysis can be applied to reveal disease-specific changes in functional connectivity in patients with Lewy body dementia or epilepsy [27], [28]. Both PLI and TE have revealed different aspects of functional connectivity concerning cognitive function in healthy as well as pathologically altered brain networks [26]- [28].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several studies have shown that TE analysis can be applied to reveal disease-specific changes in functional connectivity in patients with Lewy body dementia or epilepsy [27], [28]. Both PLI and TE have revealed different aspects of functional connectivity concerning cognitive function in healthy as well as pathologically altered brain networks [26]- [28]. However, the relationship between the PLI and TE remains unclear.…”
Section: Introductionmentioning
confidence: 99%